2013
DOI: 10.1097/qai.0b013e3182a60f36
|View full text |Cite
|
Sign up to set email alerts
|

Higher Serum Iron Is Associated With Increased Oxidant Stress in HIV-Infected Men

Abstract: Background F2-isoprostanes (F2-IsoP) are oxidant stress biomarkers that are higher in HIV-infected women than men. We explored whether the effect of hemoglobin (Hgb), serum iron, or anemia on F2-IsoP is different between HIV-infected women and men. Methods Plasma F2-IsoP were quantified by gas chromatography/mass spectrometry; clinical and laboratory data were collected at enrollment or from the medical record. Multivariable linear regression was used to assess associations between F2-IsoP and Hgb, anemia as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Multiple studies have clearly shown that levels of F 2 -IsoPs, as measured in the plasma or urine, increase in obese adults [74,96101]. F 2 -IsoPs have been positively correlated with body mass index (BMI), waist circumference (WC), visceral fat area, and percent body fat [102118]. Interestingly, recent epidemiological studies have implicated possible racial differences in the association of F 2 -IsoPs with obesity.…”
Section: Isoprostanes As Biomarkers Of Oxidative Stress In Human Dmentioning
confidence: 99%
“…Multiple studies have clearly shown that levels of F 2 -IsoPs, as measured in the plasma or urine, increase in obese adults [74,96101]. F 2 -IsoPs have been positively correlated with body mass index (BMI), waist circumference (WC), visceral fat area, and percent body fat [102118]. Interestingly, recent epidemiological studies have implicated possible racial differences in the association of F 2 -IsoPs with obesity.…”
Section: Isoprostanes As Biomarkers Of Oxidative Stress In Human Dmentioning
confidence: 99%
“…In particular, high serum iron levels are associated with increased oxidative stress in HIV-infected men. 1 As a result, the levels of cellular iron are tightly regulated. The role of iron in bacterial and fungal infections is well established [2][3][4] ; however, changes in cellular or systemic iron after HIV infection is not well understood.…”
mentioning
confidence: 99%
“…Hulgan et al [6] also found elevated plasma concentrations of F2-isoprostane in PLWHA under cART and viral suppression. Crist et al [31] showed higher 8-isoprostane levels in HIV-infected women as compared to men; therefore it is worth mentioning that, in our study, the analysis was adjusted for gender, age, and other variables that could be confounding.…”
Section: Discussionmentioning
confidence: 81%